Fuzzy Logic Based LoRa and IoT Smart Buoy for Sea Wave Monitoring in Madura - ADI KURNIAWAN SAPUTRO; RIZA ALFITA; MOHAMAD AHSAN ZUHUDI; MUTTAQIN HARDIWANSYAH; DENI TRI LAKSONO; DIAN NEIPA PURNAMASARI (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2026)
Indonesia is an archipelagic country with most of its territory consisting of water, increasing the risk of water-related natural disasters. Seawater waves, influenced by tidal movements, are one such phenomenon, and wind speed significantly affects their height. Faster sea winds can generate higher seawater waves. To obtain related data, a system capable of detecting seawater wave height and wind speed is required. This study aims to test a LoRa (Long Range)-based seawater wave detection system that is both efficient and reliable. The system uses a BNO055 sensor to measure wave height and an anemometer to detect wind speed. The relationship between wind speed and seawater wave height is analyzed using the fuzzy Mamdani method. Results show the BNO055 sensor has 92% accuracy, the anemometer 98.4%, and the fuzzy Mamdani method yields an error rate of only 0.25%. This system is expected to enhance marine monitoring and safety efforts.